Identification of alloantibody causing hemolytic disease of newborn with multiple maternal IgG antibodies - Shujaat, Wajiha; Ali, Syeda Tabeena; Hanif, Amjid (International Journal of Pathology, 2025)
Introduction: Hemolytic disease of the fetus and newborn (HDFN) results from passage of maternal alloantibodies like anti-Fya (IgG) through placenta. They attach with fetal red blood cells cause hemolysis. It is a rare but sometimes a serious health concern. Case Report: A preterm 12-day-old male child was born preterm, presented with a complaint of yellowish discoloration of skin and sclera for 5 days. He weighed 3.2 kg at birth and at the time of hospital admission the weight was 2.6kg. On examination, he was a deeply icteric child, and no active bleeding was observed. CBC showed Hb 16.2 g/dL, TLC 6x109 /L, and platelets 437x109/L. Reticulocyte counts 0.92%, and total bilirubin 19 mg/dL. Conclusion: It is suggested that once throughout the antenatal care of pregnant women minor blood group antibody screening be performed.